Nutritional status as a factor related to prolonged menstrual cycle in college students - Safitri, Debby Endayani; Rahayu, Nur Setiawati; Aini, Rahmatika Nur; Zainal, Ana Utami (Arsip Keilmuan Gizi (AKG), 2026)
Nutritional status plays an important role in the regulation of reproductive hormones; however, its association with various aspects of menstrual disorders remains inconsistent. This study aimed to examine the relationship between nutritional status and age at menarche with composite menstrual disorders and specific menstrual characteristics among female university students. A cross-sectional design was employed, involving female nutrition students from a single cohort who completed an online questionnaire. Independent variables included nutritional status (normal and abnormal) and age at menarche (early and normal). Dependent variables comprised composite menstrual disorders, menstrual duration, menstrual cycle length, and premenstrual symptoms. Data were analyzed using the chi-square test. The results showed that nutritional status was significantly associated with menstrual cycle length (p<0.027). However, no significant associations were found between nutritional status and composite menstrual disorders, menstrual duration, or premenstrual symptoms. In addition, age at menarche was not significantly associated with any of the menstrual characteristics analyzed. In conclusion, the influence of nutritional status on menstruation appears to be specific to certain aspects, particularly menstrual cycle length. The use of composite indicators of menstrual disorders may obscure more specific associations. Therefore, separating individual components of menstrual patterns is essential to achieve a more accurate understanding of the relationship between nutritional status and reproductive health in young adult women.